The study of air pollution at the present stage - Adilov Tulkin Turdimovich; Sarikulov Madraim Khasanovich (Genius Journals, 2023)
This article deals with the problem of air pollution at the present stage. The issues of atmospheric air pollution and the health of the population associated with it have been studied. Also, an analysis of atmospheric air pollution at the present stage was carried out from the point of view of preserving nature and civilization.
Keywords: Atmospheric air pollution; explosives and toxic substances; water and air pollution; UN Conference